2022
DOI: 10.1021/acsomega.2c03648
|View full text |Cite
|
Sign up to set email alerts
|

CoFe2O4 Nanoparticles Grown within Porous Al2O3 and Immobilized on Graphene Nanosheets: A Hierarchical Nanocomposite for Broadband Microwave Absorption

Abstract: Demands to develop efficient microwave-absorbing materials are increasing with the advancement of information technology and the exponential rise in the usage of electromagnetic devices. To reduce electromagnetic interference and to overcome the adverse effects caused by microwave exposure resulting from the excessive usage of electromagnetic devices, microwave absorbers are very necessary. In addition, radar-absorbing materials are essential for stealth technology in military applications. Herein, we report a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The crystalline nature of the Al 2 O 3 /Mn–Co nanocomposite was identified by the XRD pattern. Figure a shows diffraction peaks at 2θ = 19.2, 36.8, 45.7, 60.3, and 66.4°, corresponding to the crystal planes (111), (311), (400), (511), and (440) of γ-Al 2 O 3 [JCPDS No: 10–0425]. , Furthermore, the diffraction peaks that emerged at 2θ = 30.56, 36.03, 37.67, 43.8, 54.39, 57.96, and 63.68° matched well with the (220), (311), (222), (400), (422), (511), and (440) planes of MnCo 2 O 4 with a cubic crystal system [JCPDS No: 23–1237]. …”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The crystalline nature of the Al 2 O 3 /Mn–Co nanocomposite was identified by the XRD pattern. Figure a shows diffraction peaks at 2θ = 19.2, 36.8, 45.7, 60.3, and 66.4°, corresponding to the crystal planes (111), (311), (400), (511), and (440) of γ-Al 2 O 3 [JCPDS No: 10–0425]. , Furthermore, the diffraction peaks that emerged at 2θ = 30.56, 36.03, 37.67, 43.8, 54.39, 57.96, and 63.68° matched well with the (220), (311), (222), (400), (422), (511), and (440) planes of MnCo 2 O 4 with a cubic crystal system [JCPDS No: 23–1237]. …”
Section: Resultsmentioning
confidence: 71%
“…The peak located at 651 cm –1 is related to the Mn–O bond. Furthermore, the broad peak at a range of ∼1300 to 2500 cm –1 denotes the presence of γ-Al 2 O 3 . , …”
Section: Resultsmentioning
confidence: 99%
“…Figure b shows the high-resolution Cu 2p XPS spectrum, which manifested two narrow peaks at 932.7 (Cu 2p 3/2 ) and 952.5 eV (Cu 2p 1/2 ) and was devoid of any satellite peaks. , These indicated the oxidation state of Cu in Cu 2 O–PC TW composite to be (+1). The O 1s XPS spectrum was deconvoluted into two peaks at 530.8 and 532 eV representing Cu–O bonds and surface functional groups consisting of oxygen, respectively (Figure c). , In the C 1s XPS spectrum (Figure d), the binding energy peaks corresponding to C–C, C–O, and O–CO appeared at 284.6, 286.4, and 288.4 eV, respectively. , The XPS analysis data of the pure Cu 2 O is presented in Figure S6. It was observed that compared to pure Cu 2 O, the binding energies of Cu 2p in the Cu 2 O–PC TW composite showed a negative shift of ∼0.1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…2e displays the O 1s XPS spectrum, which was deconvoluted into two peaks, representing M–O–M (531.3 eV) and oxygen-containing functional groups (533.1 eV). 44 The high-resolution F 1s XPS spectrum is shown in Fig. 2f, which consists of two peaks at 685.7 and 688.8 eV, corresponding to F–Ti and F–O, respectively.…”
Section: Resultsmentioning
confidence: 99%